1998
DOI: 10.1023/a:1005874206814
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of an intravenous (i.v.) injection of the bradykinin analog RMP-7 (100 ng/kg) were assessed in normal dogs and dogs with focal, radiation-induced brain lesions. A dose of 20 Gy was delivered to a point 0.75 cm from a removable interstitial 125I source; parameters relating to blood flow and permeability were quantified using computed tomography 2-8 weeks after irradiation. Blood flow-related endpoints included regional cerebral blood flow (rCBF), mean transit time of blood and vascular volume, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Intra-arterial RMP-7 caused no BBBD in normal brain in humans [212], which is consistent with an abluminal expression of the BK receptor. Intravenous administration of RMP-7 caused no BBBD in dogs [213] or rats [214]. Intravenous RMP-7 did not increase the clinical efficacy of carboplatin in a RCT of malignant glioma [215].…”
Section: Bbbd With Intra-arterial Bradykinin Analogsmentioning
confidence: 88%
“…Intra-arterial RMP-7 caused no BBBD in normal brain in humans [212], which is consistent with an abluminal expression of the BK receptor. Intravenous administration of RMP-7 caused no BBBD in dogs [213] or rats [214]. Intravenous RMP-7 did not increase the clinical efficacy of carboplatin in a RCT of malignant glioma [215].…”
Section: Bbbd With Intra-arterial Bradykinin Analogsmentioning
confidence: 88%
“…, 27 (55%), investigate BBB disruption in rats [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] . In addition, eleven (22%) studies use mice [12] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , five involve rabbits [88] , [89] , [90] , [91] , [92] , two include dogs [93] , [94] , two describe monkeys [95] , [96] , one article studied the effects of RT on the BBB in sharks [97] and one in pigs [98] .…”
Section: Resultsmentioning
confidence: 99%
“…Radiation therapy is part of the standard treatment paradigm for CNS tumors [ 57 ]. The short-term effects of prior radiotherapy on the BBB opening induced by Labradimil have been investigated in normal and focal-irradiated dog brains [ 58 ]. Results showed that a single, early i.v.…”
Section: Discussionmentioning
confidence: 99%